2020
DOI: 10.1002/jaba.682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a treatment without extinction for elopement maintained by access to stereotypy

Abstract: Elopement is a common and potentially dangerous form of problem behavior. Results of a functional analysis found that the elopement of a child with autism was maintained by access to stereotypy in the form of door play. We implemented functional communication training and contingency‐based delays dependent on the absence of elopement and increased the amount of time the participant waited prior to engaging in stereotypy. We also conducted treatment‐extension probes, with the participant waiting up to 10 min wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We are somewhat limited in interpreting similarities in these outcomes with previous CBPD studies due to DRA‐ and DRO‐based thinning procedures often being combined into a single treatment package (e.g., Beaulieu et al, 2018; Hanley et al, 2014; Rose & Beaulieu, 2019) or evaluated individually without comparison (e.g., Boyle et al, 2020; Jessel et al, 2018b; Santiago et al, 2015). Ghaemmaghami et al (2016) included the only other comparative evaluation of CBPD procedures with a single participant, Will, and found that although both reduced problem behavior, the DRA‐based thinning procedure was more effective and improved contextually appropriate behavior.…”
Section: Discussionmentioning
confidence: 78%
“…We are somewhat limited in interpreting similarities in these outcomes with previous CBPD studies due to DRA‐ and DRO‐based thinning procedures often being combined into a single treatment package (e.g., Beaulieu et al, 2018; Hanley et al, 2014; Rose & Beaulieu, 2019) or evaluated individually without comparison (e.g., Boyle et al, 2020; Jessel et al, 2018b; Santiago et al, 2015). Ghaemmaghami et al (2016) included the only other comparative evaluation of CBPD procedures with a single participant, Will, and found that although both reduced problem behavior, the DRA‐based thinning procedure was more effective and improved contextually appropriate behavior.…”
Section: Discussionmentioning
confidence: 78%
“…The latency‐based IISCA has since been replicated with additional participants exhibiting elopement (e.g., Boyle et al, 2020), but extensions of this format to other dangerous problem behavior topographies are limited to one participant in Lambert et al (2017), who engaged in severe aggression and self‐injury. However, this participant did not emit problem behavior during the analysis and treatment data were not included in the publication, so little can be said about the efficacy of the latency‐based IISCA for populations with other forms of severe problem behavior.…”
Section: Latency‐based Iisca Formatmentioning
confidence: 99%
“…This model of functional analysis has been replicated in several hundred studies (Beavers et al, 2013;Hanley et al, 2003). It has been used in assessing the operant function of other topographies of problem behavior besides self-injury (e.g., aggression, property destruction, inappropriate vocalizations, elopement, food refusal, and stereotypy; e.g., Bachmeyer et al, 2019;Boyle & Adamson, 2017;Fisher et al, 2013;Hausman et al, 2020;Saini et al, 2019;Shawler et al, 2020;Wunderlich et al, 2020). It has also been used to illustrate the flexibility of test conditions for other unique sources of social positive reinforcement (e.g., access to leisure items and food) and social negative reinforcement (e.g., the termination of social interactions, medical routines, and loud noises; Harper et al, 2013;Iwata, Pace et al, 1990;McCord et al, 2001;Schlichenmeyer et al, 2013;Tiger et al, 2009).…”
mentioning
confidence: 97%
“…It has also been used to illustrate the flexibility of test conditions for other unique sources of social positive reinforcement (e.g., access to leisure items and food) and social negative reinforcement (e.g., the termination of social interactions, medical routines, and loud noises; Harper et al, 2013; Iwata, Pace et al, 1990; McCord et al, 2001; Schlichenmeyer et al, 2013; Tiger et al, 2009). Further, this model of functional analysis can capture complex environmental contingencies, such as property destruction maintained by access to stereotypic object manipulation (Boyle et al, 2020; Fisher et al, 1998), SIB maintained by access to self‐restraint (Scheithauer et al, 2015; Smith et al, 1996; Vollmer & Vorndran, 1998), aggression reinforced by compliance with children's demands (Bowman et al, 1997; Owen et al, 2020), and aggression maintained by escape to a preferred activity (Call et al, 2005). The recommended approach has been to assess problem behavior's sensitivity to single or isolated contingencies initially and then to progress to more complex analyses only after simpler and more common explanations have been ruled out (Carr et al, 2009; Iwata, 1994).…”
mentioning
confidence: 99%